Pertumbuhan Produksi dan Segregasi Tanaman Generasi F3 yang Diseleksi dari Persilangan Cabe Keriting dan Rawit - Halimi, E. S.; Zaidan, Zaidan; Susilawati, Susilawati; Adriansyah, Fikri; Cahyani, Assifa I.; Panjaitan, Mega S.; Agustina, Peni; Nuraini, Habibah (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2023)
Halimi, E.S., Zaidan, Z., Susilawati, S., Adriansyah, F., Cahyani, A.I., Panjaitan, M.S., Agustina, P., & Nuraini, H. (2023). Growth yield and segregation of several f3 generation of pepper accessions selected from the cross of curly and cayenne peppers. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-11 Tahun 2023, Palembang 21 Oktober 2023. (pp. 358-369). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Suboptimal land, in general, refers to condition of the land not prefectly suitable for cultivation, including those containing propagul caused disease infestation. On pepper cultivation, very often occurs disease infestation such as antracnose desease. Crossing curly and cayenne peppers was intended to obtain accessions of curly pepper having fruit position upward such as in cayenne pepper that capable of avoiding several diseases infestation. The F3-seeds were prepared 3 years prior to this research with selection to choose plant genotypes having fruit position upward. Research was done in-cooperation with farmer at Kecamatan Gunung Megang, Muaraenim on December 2022 to May 2023 based on Randomized Block Design with two accessions and three blocks with 10-15 plants per plot. Research indicated that both accessions showed good growth and yield with relatively similar harvesting period and yield potential. Interestingly, we observed several recombinat plants having fruit shape identical to curly peppers with fruit position upward. The plants of CK3(2)xCR3(6) accession, however had more slender fruit shape as compared to CK6(8)xCR6(4) accession. Furthermore observation indicated the presence of segregation of this character. Accession of CK3(2)xCR3(6) showed higher segregation value of 50% than CK6(8)xCR6(4) accession with segregation value of 25%.